1997
DOI: 10.1021/ma970306z
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Random Coils:  Rotationally Confined Chain Molecules

Abstract: Considered are chain molecules characterized by rotational potentials with a set of low energy states separated by large energy barriers. The expectation is that such chain molecules should exhibit unique properties. Polynorbornene and laterally substituted polynorbornenes are characteristic examples. Simulations based on ab initio methods, semiempirical quantum mechanical methods, and force field methods are employed in order to derive information on the chain conformation and dynamics of the polynorbornenes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 20 publications
1
46
0
1
Order By: Relevance
“…Based on this data and according to molecular dynamic simulation data performed by Wendorff and collaborators, a rigid random coil conformation is expected for homopolynorbornene [5].…”
Section: Structural Characterisationmentioning
confidence: 66%
See 1 more Smart Citation
“…Based on this data and according to molecular dynamic simulation data performed by Wendorff and collaborators, a rigid random coil conformation is expected for homopolynorbornene [5].…”
Section: Structural Characterisationmentioning
confidence: 66%
“…Depending on the catalytic system and on the experimental synthesis conditions different polynorbornenes may be obtained ranging from amorphous to more stereoregular and crystalline ones. Based on molecular dynamic simulations Wendorff and collaborators [4][5][6] have shown that amorphous polynorbornene assumes a rigid random coil conformation. This peculiar structural feature suggests many interesting properties.…”
Section: Introductionmentioning
confidence: 99%
“…4 -6 Molecular dynamic simulations have shown that PNBs display a characteristic rigid random-coil conformation and restricted rotation around the main chain. 7,8 According to their peculiar structure, these polymers exhibit very high decomposition temperature, high thermal stability, excellent dielectric properties, and unusual transport properties. Therefore, they are attractive materials not only for microelectronics and optical applications 7 but also for other potential applications in packing and gas separation.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules of this type have been termed "single chain glasses" for this reason 2) . Substituted polynorbornenes such as poly(5-norbornene-2-carboxylic esters) 3) and poly(5-norbornadiene-2,3-dicarboxylic esters) 4) also correspond to this type of chain molecules displaying a rigid statistical chain conformation 5) even at elevated temperatures. In the present communication, we report on the vinylic polymerisation of exo N-o/m/p tolyl (Io/Im/Ip)-nadimides using a Pd(II) catalyst.…”
Section: Introductionmentioning
confidence: 99%